Exact solutions of a class of nonlinear dispersive long wave systems via Feng's first integral method - Lu, Qiuci; Zhang, Songchuan; Zheng, Hang (AIMS mathematics, 2021)
In this paper, eight groups of exact solutions for the (1+1)-dimensional and (2+1)-dimensional nonlinear dispersive long wave systems are found respectively via Feng's first integral method. It is shown that there are some similarities in the expressions of the solutions of (1+1)-dimensional and (2+1)-dimensional DLWEs, while there exist some differences in their dimensions and their physical significance. Finally, some graphs are presented to show these features, which also show the effectiveness of the proposed method.